First record of the quarantine pest Atherigona ( Atherigona ) oryzae Malloch (Diptera: Muscidae) in Korea - Suh, Sang Jae; Kwon, Yong Jung (Entomological research, 2018)
Occurrence of the invasive quarantine pest fly, Atherigona ( Atherigona ) oryzae Malloch, is hereby recorded for the first time in Gyeongsangbuk‐do Province, Korea. Morphological characteristics for accurate identification of the species, a list of hosts, and damage patterns are described to provide plant quarantine information for pest management.